Cream Strategy and Its Crucial Role In Foreign Language Learning - Mamatkulova Nilufar Fayzullakulovna (Penerbit Jurnal Indonesia, 2024)
Educating future foreign language teachers using the CREAM strategy significantly enhances their language skills. This article explores the CREAM strategy, a valuable approach for language learners, and examines its importance in language acquisition.